1985
DOI: 10.1099/00222615-19-2-247
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Bordetella Bronchiseptica in the Porcine Respiratory Tract

Abstract: SUMMARY.The virulence of Bordetella bronchiseptica in gnotobiotic piglets was studied by intranasal infection with 11 cultures derived from eight strains isolated from pigs (4), dogs (2), a human subject and a monkey. Six of the cultures contained organisms in phase I and five contained phenotypically different phase-I11 or -1V organisms. Of the phase-I11 and -1V cultures, four were derived from strains that had been isolated in phase I. Colonisation of the nasal cavity was investigated by counting bacteria in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These results suggest that B. bronchiseptica is an opportunistic pathogen of cats, and that the likelihood of a particular B. bronchiseptica isolate producing disease is probably related to host or environmental factors such as crowding, stress and hygiene [36]. It may also be related to differential expression of virulence determinants as has been demonstrated for canine or porcine infections where phase variation occurs [37,38].…”
Section: Discussionmentioning
confidence: 89%
“…These results suggest that B. bronchiseptica is an opportunistic pathogen of cats, and that the likelihood of a particular B. bronchiseptica isolate producing disease is probably related to host or environmental factors such as crowding, stress and hygiene [36]. It may also be related to differential expression of virulence determinants as has been demonstrated for canine or porcine infections where phase variation occurs [37,38].…”
Section: Discussionmentioning
confidence: 89%
“…It follows, therefore, that the specific mechanisms used for adherence by these two pathogens may differ. Additionally, strains of B. bronchiseptica isolated from a specific host often display a reduced ability to colonize or induce disease in heterologous species (11,25,37), suggesting there may be host-specific differences in colonization factors of B. bronchiseptica strains as well. Thus, studies on adhesion of B. bronchiseptica in a particular host species are most meaningful when performed with relevant target cells from that species.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have also noted a positive correlation between DNT activity or mouse lethality of B. bronchiseptica strains and the ability of those strains to produce respiratory disease in pigs (4, 6). Collings and Rutter (4) noted that strains of B. bronchiseptica which produced turbinate atrophy in experimentally infected piglets had a much lower 50% lethal dose in mice than did avirulent strains. Elias et al (6) demonstrated that B. bronchiseptica strains isolated from herds of pigs suffering from IAR had a considerably higher average level of mouse toxicity than did strains isolated from nonaffected herds.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be considerable variation among B. bronchiseptica strains in their ability to colonize and produce turbinate atrophy and pneumonic lesions in young pigs (4,24). This situation has important implications in the treatment of commercial pig herds colonized by B. bronchiseptica.…”
mentioning
confidence: 99%